2010
DOI: 10.1063/1.3309713
|View full text |Cite
|
Sign up to set email alerts
|

Low-dimensional Mott material: Transport in ultrathin epitaxial LaNiO3 films

Abstract: Electrical resistivity and magnetotransport are explored for thin (3–30 nm), epitaxial LaNiO3 films. Films were grown on three different substrates to obtain LaNiO3 films that are coherently strained, with different signs and magnitude of film strain. It is shown that d-band transport is inhibited as the layers progress from compression to tension. The Hall coefficient is “holelike.” Increasing tensile strain causes the film resistivity to increase, causing strong localization to appear below a critical thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

18
180
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(199 citation statements)
references
References 20 publications
18
180
1
Order By: Relevance
“…A key prediction of our work is a strong site dependence of the local magnetic susceptibility, with one sublattice exhibiting a Curie be-havior and the other a temperature independent χ. The transition we have identified may be related to the insulating behavior observed in few-layer LaNiO 3 -based heterostructures [25,26] where DFT+U calculations [26,27] suggest that disproportionation can occur and drive a transition.…”
mentioning
confidence: 99%
“…A key prediction of our work is a strong site dependence of the local magnetic susceptibility, with one sublattice exhibiting a Curie be-havior and the other a temperature independent χ. The transition we have identified may be related to the insulating behavior observed in few-layer LaNiO 3 -based heterostructures [25,26] where DFT+U calculations [26,27] suggest that disproportionation can occur and drive a transition.…”
mentioning
confidence: 99%
“…However, we believe that our elastic parameters pretty reliably describe monoclinic LaNiO 3 as long as the thickness of the film is sufficiently large to prevent from the occurrence of metal-to-insulator transition. Experimental investigation of electrical resistivity [52] and electronic structure [53] has revealed that films that are thick enough (10 nm or somewhat less depending on the substrate) show clearly pro-nounced metallic behaviour that is typical for bulk LaNiO 3 and can be properly represented at DFT level. But for the ultrathin LaNiO 3 films composed of only several monolayers, a metal-to-insulator transition is observed and a standard DFT scheme fails to reproduce it [53].…”
mentioning
confidence: 99%
“…These three regimes also pertain to films grown on different substrates, such as LaAlO 3 , NdGaO 3 , KTaO 3 , and MgO (as well as LaAlO 3 , LSAT and DyScO 3 in Ref. [14]). We may conclude that the LNO films undergo a MI transition upon reducing the number of layers and that strong localization effects are seen in the 5 u.c.…”
mentioning
confidence: 99%